269 PHARMACIST INTERVENTIONS WITHIN A MULTIDISCIPLINARY CARE TEAM FOR FRAIL OLDER ADULTS PRESENTING TO A LEVEL 4 EMERGENCY DEPARTMENT. (25th October 2022) - O'Caheny, C; Dillon, L; Smyth, H; Riches, R; Laguna, R; Magner, S; Pender, C; Carrabine, N; Buckley, B; Carey, S; Harrington, G; Mitchell, M; et al.
Abstract: Background: Inappropriate polypharmacy and 'Potentially Inappropriate Prescriptions' (PIP) are associated with increased morbidity and hospitalisation, in particular among frail older persons. A structured medication review, in conjunction with a Comprehensive Geriatric Assessment (CGA), can address PIP. The aim of the study was to review Frail Intervention Team (FIT) pharmacist interventions for frail, older adults presenting to the Emergency Department (ED) and experiencing medication compliance difficulties, polypharmacy and PIP. Methods: Patients identified for medication review included those experiencing polypharmacy or medication compliance issues, presenting with a fall, delirium and/or frailty syndromes or complex comorbidities. The medication review process involved completion of medicines reconciliation and medication appropriateness review in accordance with the 7-Steps Medication Review Model (Scottish Government Polypharmacy Model of Care Group, 2018). Pharmacist optimisation recommendations were reviewed by a Consultant Geriatrician or Registrar and discussed with the patient prior to implementation. Results: The FIT Pharmacist completed medication reviews for 765 patients between May 2021 and April 2022. The mean age (+/-SD) was 83.1 (+/-7.0) years with a median Clinical Frailty Score (CFS) of 5 (mildly/moderately frail). Medication Optimisation recommendations were actioned in 63% (n=483) of patients reviewed. The most commonly encountered PIP's included: excessive anti-hypertensive/diuretic therapy, long-term acid-suppression therapy, anticholinergics and long-term prophylactic antimicrobials. Prescribing opportunities identified included: bone protection, laxatives and pain management. Conclusion: FIT pharmacist review, in conjunction with the CGA, led to medication optimisation interventions in the frail older adult cohort presenting to the ED. Future studies should examine the impact of medication review on patient outcomes post-discharge.